Serotonin stimulates female preoptic area kisspeptin neurons via activation of type 2 serotonin receptors in mice - Buo, Carrie; Bearss, Robin J.; Novak, Alyssa G.; Anello, Anna E.; Dakin, Jordan J.; Piet, Richard (Frontiers in Endocrinology, 2023)
The neuroendocrine control of ovulation is orchestrated by neuronal circuits that ultimately drive the release of gonadotropin-releasing hormone (GnRH) from the hypothalamus to trigger the preovulatory surge in luteinizing hormone (LH) secretion. While estrogen feedback signals are determinant in triggering activation of GnRH neurons, through stimulation of afferent kisspeptin neurons in the rostral periventricular area of the third ventricle (RP3VKISS1 neurons), many neuropeptidergic and classical neurotransmitter systems have been shown to regulate the LH surge. Among these, several lines of evidence indicate that the monoamine neurotransmitter serotonin (5-HT) has an excitatory, permissive, influence over the generation of the surge, via activation of type 2 5-HT (5-HT2) receptors. The mechanisms through which this occurs, however, are not well understood. We hypothesized that 5-HT exerts its influence on the surge by stimulating RP3VKISS1 neurons in a 5-HT2 receptor-dependent manner. We tested this using kisspeptin neuron-specific calcium imaging and electrophysiology in brain slices. We show that exogenous 5-HT reversibly increases the activity of the majority of RP3VKISS1 neurons. This effect is more prominent in females than in males, is likely mediated directly at RP3VKISS1 neurons and requires activation of 5-HT2 receptors. The functional impact of 5-HT on RP3VKISS1 neurons, however, does not significantly vary during the estrous cycle. Taken together, these data suggest that 5-HT2 receptor-mediated stimulation of RP3VKISS1 neuron activity might be involved in mediating the influence of 5-HT on the preovulatory LH surge.